Particulate Matter Emission from Combustion and Non-Combustion Automotive Engine Process: Review and Computational Bibliometric Analysis on Its Source, Sizes, and Health and Lung Impact - Nandiyanto, Asep Bayu Dani; Ragadhita, Risti; Setiyo, Muji; Obaidi, Abdulkareem Sh. Mahdi Al; Hidayat, Arif (Automotive Experiences, 2023)
This study aimed to comprehensively analyze particulate matter (PM) emissions from vehicles, focusing on their sources based on combustion and non-combustion process, classification (PM10, PM2.5, PM0.1), and health implications (including PM transportation into lungs). Employing bibliometric analysis, we assessed the growth of scientific publications related to PM, identifying top-cited works based on citations, publisher, author, country, and affiliation. We also visually mapped the development of research in this field using keyword-based publication data from Scopus (2019-2023) with the keywords "particulate matter", "emission”, and "particle size" by utilizing Publish or Perish and VOSviewer software. Our findings underscore a significant uptrend in particulate matter research, shedding light on key areas of investigation. This study serves as a valuable resource for academics seeking research direction and a reference point for future investigations.